PENYEDIAAN PAPAN SKOR DAN INSTALASI LAMPU SEBAGAI SARANA PENDUKUNG OLAHRAGA DI DESA KARANG INDAH - Irpan, Irpan; Ridlo, Azi Faiz (An-Nizam, 2024)
Badminton is a highly popular sport in Indonesia, yet many rural courts lack essential support facilities, such as scoreboards and adequate lighting. These elements are crucial for ensuring the smooth flow and quality of the game during both practice and competition. The program aimed to improve the badminton court in Karang Indah village by providing a modern scoreboard and installing proper lighting. The project involved planning, material procurement, installation, and testing phases. The scoreboard enhanced the accuracy and ease of tracking match scores, while the lighting improved player visibility, especially during night games. The results showed a significant improvement in both the comfort and quality of gameplay, benefiting players, referees, and spectators alike. This initiative serves as a model for similar rural areas, promoting broader community participation in badminton and fostering a healthier, more active lifestyle.